2019
DOI: 10.1002/spe.2703
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of pure spectrum‐based fault localization techniques for large‐scale software systems

Abstract: Pure spectrum-based fault localization (SBFL) is a well-studied statistical debugging technique that only takes a set of test cases (some failing and some passing) and their code coverage as input and produces a ranked list of suspicious program elements to help the developer identify the location of a bug that causes a failed test case. Studies show that pure SBFL techniques produce good ranked lists for small programs. However, our previous study based on the iBugs benchmark that uses the AspectJ repository … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Thus, SBFL cannot distinguish between program elements that exhibit the same execution patterns. The reason behind this issue is that SBFL techniques leverage hit spectra (i.e., whether an element is executed or not) only as the abstraction for program executions without considering any other useful contextual information [147]. In other words, they represent a program's behavior as an abstract hit spectra model that cannot capture the semantics of each program element individually [44].…”
Section: R No Contextual Informationmentioning
confidence: 99%
“…Thus, SBFL cannot distinguish between program elements that exhibit the same execution patterns. The reason behind this issue is that SBFL techniques leverage hit spectra (i.e., whether an element is executed or not) only as the abstraction for program executions without considering any other useful contextual information [147]. In other words, they represent a program's behavior as an abstract hit spectra model that cannot capture the semantics of each program element individually [44].…”
Section: R No Contextual Informationmentioning
confidence: 99%
“…Elements with high scores are placed at the beginning of the list, and elements with low scores are placed at the bottom. Heiden et al (2019) argue that the SBFL technique only exploits the program spectrum as an abstraction for program execution without considering any other useful contextual information. Vancsics et al (2021) addresses this problem by using method call frequency.…”
Section: Related Workmentioning
confidence: 99%
“…Notably, their evaluation results shows that results on artificial faults do not predict results on real faults for both techniques, and a hybrid technique is significantly better than both techniques. Keller et al (2017) and Heiden et al (2019) evaluated the effectiveness of statistical fault localization on real world large-scale software systems. The authors found that, for realistic large-scale programs, the accuracy of statistical debugging is not suitable for human developers.…”
Section: Evaluation Of Fault Localization Techniquesmentioning
confidence: 99%